Cardiopulmonary bypass-assisted surgery for the treatment of Xp11.2 translocation/TFE3 gene fusion renal cell carcinoma with a tumor thrombus within the inferior vena cava: A case report - ZHU, GUANCHEN (Oncol Lett, 2015)
Renal cell carcinoma (RCC) accounts for 85–90% of kidney cancers, which in turn account for 2–3% of all malignant tumors in adults. Xp11.2 translocation/TFE3 gene fusion RCC is currently classified as a distinct type of RCC. RCC is capable of invading the renal vein and inferior vena cava to form a tumor thrombus. The incidence of RCC with tumor thrombi within the renal vein or inferior vena cava is 7–10% in China. In the present case report, the patient underwent radical resection of the renal tumor and removal of the tumor thrombus, assisted by cardiopulmonary bypass, for the treatment of Xp11.2 translocation/TFE3 gene fusion RCC. The patient was followed-up for 12 months subsequent to treatment. The patient's renal function remained within the normal range, and computed tomography examination revealed no evidence of disease recurrence or metastases. The present case report aimed to provide a reference for the development of guidelines for the diagnosis and treatment of Xp11.2 translocation/TFE3 gene fusion RCC.